Complete Chloroplast Genomes of Acanthochlamys bracteata (China) and Xerophyta (Africa) (Velloziaceae): Comparative Genomics and Phylogenomic Placement - Wanga, Vincent Okelo; Dong, Xiang; Oulo, Millicent Akinyi; Mkala, Elijah Mbandi; Yang, Jia-Xin; Onjalalaina, Guy Eric; Gichua, Moses Kirega; Kirika, Paul Muigai; Gituru, Robert Wahiti; Hu, Guang-Wan; Wang, Qing-Feng (Frontiers in Plant Science, 2021)
Acanthochlamys P.C. Kao is a Chinese endemic monotypic genus, whereas Xerophyta Juss. is a genus endemic to Africa mainland, Arabian Peninsula and Madagascar containing ca.70 species. In this study, we sequenced the complete chloroplast (cp) genomes of Acanthochlamys bracteata and did a comparative study with the African Xerophyta species (Xerophyta spekei and Xerophyta viscosa) present in the NCBI database. A typical quadripartite structure was detected with a genome size from 153,843bp to 155,498bp, consisting of a large-copy (LSC) and small single-copy (SSC) regions separated by a pair of inverted repeats (IR regions). The total number of genes found in A. bracteata, X. spekei and X. viscosa cp genomes were 129, 130, and 132 respectively. Approximately 50, 29, 28 repeats and 90, 59, 53 simple sequence repeats were found in the A. bracteata, X. spekei, and X. viscosa cp genome, respectively. Nucleotide diversity among all species was estimated to be 0.03501, the average Ka/Ks ratio 0.26, and the average K2P value 0.0831. Genomic characterization was undertaken be comparing the genomes of the three species of Velloziaceae implicating conserved features in the coding regions, but variability in the junctions of IRs/SSC regions and the divergent hotspot regions potentially used the DNA markers. Phylogenetic analysis suggests that A. bracteata species has a closer genetic relationship to the genus Xerophyta. The present study is the first to obtain complete genomic of A. bracteata and give a genomic comparative study with the African species of Xerophyta. Thus, can be useful in developing lineage-specific markers for genetic diversity and evolution studies in Velloziaceae.